Imbalanced nutrition and increased dietary inflammatory index in children with autism spectrum disorder: associations with neurodevelopmental disorders - Shen, Jing; You, Junqiao; Wang, Wenjing; Yang, Wenli; Zhao, Wenli; Zhao, Jianan; Ding, Huini; Xi, Yuandi; Huang, Hongmei (Frontiers in Nutrition, 2025)
BackgroundThe incidence rate of autism spectrum disorders (ASDs) has been rising; this study aimed to explore the relationship between nutritional intake and neurodevelopment in children with ASDs.MethodsThis study is a case–control cross-sectional comparison including 50 children with ASDs and 50 typically developing controls. A total of 500 children with neurodevelopmental disorders and 500 typically developing (TD) children were recruited based on clinical diagnosis to compare levels of inflammation. Among them, 50 children were diagnosed with ASDs based on DSM-5 criteria by experienced developmental behavioral pediatricians. A total of 50 typically developing children were matched with the 50 children with ASDs. Dietary surveys, Autism Diagnostic Observation Schedule (ADOS), and physical development evaluations were conducted on these 100 children.ResultsThe children’s dietary inflammatory index (C-DII), systemic immune inflammatory index (SII), and systemic inflammatory response index (SIRI) in the ASD group were significantly higher compared to the TD group (p<0.05). A positive correlation was observed between C-DII and SII (r = 0.323, p = 0.022), as well as SIRI (r = 0.283, p = 0.046). The dietary diversity in the ASD group was lower than that of the TD group, with a higher prevalence of picky eating behaviors in the ASD group. After adjusting for demographic characteristics, the C-DII may be correlated with ASD [odds ratio (OR) = 1.842, 95% confidence interval (CI) = 1.114 ~ 3.046, p = 0.017].ConclusionChildren with autism spectrum disorders (ASD) displayed higher C-DII scores. The results of this study suggest that there may be a correlation between C-DII and the neurodevelopment of children with ASD, not causality. Inflammatory dietary patterns may represent a modifiable factor linked to neurodevelopmental outcomes.